Smith Multiples of a Class of Primes with Small Digital Sum: Amin Witno - Team, Support (Thai Journal of Mathematics, 2016)
Using prime numbers whose digits are zeros and ones, we demonstrate how to construct integers m for which mP is a Smith number for any prime P with a fixed, small digital sum. Conversely, using numbers with small digital sums, we can obtain Smith multiples of a given prime whose digits are zeros and ones. Our approach relies on small digital sums in order that every multiplication process is free from carries.